2016
DOI: 10.1186/s40809-016-0019-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular 4DFlow MRI (Phase Contrast MRA): emerging clinical applications

Abstract: Recent advances in 4DFlow MRI (Phase Contrast MRA) acquisition and reconstruction enable high resolution exams to be obtained in practical imaging times. 4DFlow MRI provides images of vascular morphology and quantitative measurements of blood velocity throughout a 3D imaging volume. Hemodynamic parameters such as flow volume, relative wall shear stress, streamlines, vorticity and pressure gradients can be derived from the velocity data. The combination of anatomic vessel wall imaging, lumen visualization and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 82 publications
0
29
0
Order By: Relevance
“…The study of hemodynamic alterations in patients with cerebrovascular disease is important to understand the disease, potentially improving diagnostic capabilities and therapeutic planning. There is a demand for noninvasive imaging of cerebrovascular territories; therefore, new emerging techniques for evaluation cerebrovascular hemodynamics and CBF [ 88 ], including four-dimensional (4D) flow MRI [ 89 , 90 , 91 , 92 ]; 2D phase contrast MRI (PC-MRI) [ 93 , 94 , 95 ] and magnetic resonance black-blood thrombus imaging technique (MRBTI) [ 96 ] are being developed.…”
Section: Magnetic Resonance Imaging (Mri) and Other Similar Technimentioning
confidence: 99%
“…The study of hemodynamic alterations in patients with cerebrovascular disease is important to understand the disease, potentially improving diagnostic capabilities and therapeutic planning. There is a demand for noninvasive imaging of cerebrovascular territories; therefore, new emerging techniques for evaluation cerebrovascular hemodynamics and CBF [ 88 ], including four-dimensional (4D) flow MRI [ 89 , 90 , 91 , 92 ]; 2D phase contrast MRI (PC-MRI) [ 93 , 94 , 95 ] and magnetic resonance black-blood thrombus imaging technique (MRBTI) [ 96 ] are being developed.…”
Section: Magnetic Resonance Imaging (Mri) and Other Similar Technimentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of 4D flow MRI for the evaluation of intracranial hemodynamics. [25][26][27][28][29] 4D flow MRI, time-resolved 3D PC MRI with 3-directional velocity encoding, allows velocity measurements across the cerebral vasculature with a single scan. 30,31 4D flow MRI has been previously applied for measuring cerebrovascular flow 27,[32][33][34] and shown to be consistent with 2D PC MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the feasibility of 4D flow MRI for the evaluation of intracranial hemodynamics . 4D flow MRI, time‐resolved 3D PC MRI with 3‐directional velocity encoding, allows velocity measurements across the cerebral vasculature with a single scan .…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the relationship between intracranial vessel flow and cerebral perfusion was previously challenging because of practical limitations, including motion artifacts, lengthy scan times, and complex implementation [11]. However, a recently developed 4D‐flow MRI technique termed phase‐contrast vastly undersampled isotropic projection (PC VIPR) imaging uses radial undersampling, allowing for improved temporal and spatial resolution compared with 2D methods in clinically feasible scan times [12,13].…”
Section: Introductionmentioning
confidence: 99%